Subepithelial Hyalinisation Predicts Recurrence of Unicystic Ameloblastomas - Dominic Augustine; Roopa S. Rao; Lakshminarayana Surendra; Bharti Gupta; Thuckanaickenpalayam Ragunathan Yoithapprabhunath; Pradeep Kumar Yadalam; Shazia Mushtaq; Zeeshan Hera Ahmed; Shankargouda Patil (Diagnostics, 2022)
The inductive effect of hyalinisation and its influence on the biologic behaviour of ameloblastoma variants represent a scarcely researched domain of oral pathology. The complexity of the induction effects within the odontogenic apparatus, with the involvement of both ectodermal and mesodermal tissues, is responsible for diverse histopathological characteristics, hyalinisation being the major feature. The present study aims to deduce for the first time the correlation between the severity of hyalinisation (SOH) and recurrence in three unicystic ameloblastoma (UA) variants, namely, intra-luminal (UA-IL), luminal (UA-L) and mural (UA-M). Retrospectively diagnosed archival cases of UA-IL (n = 08), UA-L (n = 22) and UA-M (n = 30) were assessed for SOH and its correlation with recurrence. A subgroup comparison (between UA-IL/UA-L and UA-M) was also performed. The clinical parameters of the patients were also analysed from files for clinicopathological correlation with recurrence. Results: sub-epithelial hyalinisation (SEH) significantly correlated with the recurrence of UA-L and UA-M (p = 0.001). When the histologic types (UA-L and UA-IL vs. UA-M) were grouped and the correlation of SOH with recurrence was checked, it was observed that both groups (p = 0.001) showed strong statistical correlation. UA-M lesions with multilocular radiolucency (p = 0.001) also showed significant correlation with recurrence. SOH can be a reliable histological predictor of recurrence and of aggressive biologic behaviour in UA. The present study shows a significant association of hyalinisation with the biologic behaviour of UA. Further studies with immunohistochemical investigations could validate the presence of hyalinisation and identify the origin of the hyalinised product in UAs.